Metformin Is a Direct SIRT1-Activating Compound: Computational Modeling and Experimental Validation - Cuyàs, Elisabet; Verdura, Sara; Llorach-Parés, Laura; Fernández-Arroyo, Salvador; Joven, Jorge; Martin-Castillo, Begoña; Bosch-Barrera, Joaquim; Brunet, Joan; Nonell-Canals, Alfons; Sanchez-Martinez, Melchor; Menendez, Javier A. (Frontiers in Endocrinology, 2018)
Metformin has been proposed to operate as an agonist of SIRT1, a nicotinamide adenine dinucleotide (NAD+)-dependent deacetylase that mimics most of the metabolic responses to calorie restriction. Herein, we present an in silico analysis focusing on the molecular docking and dynamic simulation of the putative interactions between metformin and SIRT1. Using eight different crystal structures of human SIRT1 protein, our computational approach was able to delineate the putative binding modes of metformin to several pockets inside and outside the central deacetylase catalytic domain. First, metformin was predicted to interact with the very same allosteric site occupied by resveratrol and other sirtuin-activating compounds at the amino-terminal activation domain of SIRT1. Second, metformin was predicted to interact with the NAD+ binding site in a manner slightly different to that of SIRT1 inhibitors containing an indole ring. Third, metformin was predicted to interact with the C-terminal regulatory segment of SIRT1 bound to the NAD+ hydrolysis product ADP-ribose, a “C-pocket”-related mechanism that appears to be essential for mechanism-based activation of SIRT1. Enzymatic assays confirmed that the net biochemical effect of metformin and other biguanides such as a phenformin was to improve the catalytic efficiency of SIRT1 operating in conditions of low NAD+ in vitro. Forthcoming studies should confirm the mechanistic relevance of our computational insights into how the putative binding modes of metformin to SIRT1 could explain its ability to operate as a direct SIRT1-activating compound. These findings might have important implications for understanding how metformin might confer health benefits via maintenance of SIRT1 activity during the aging process when NAD+ levels decline.